Relationship between xerostomia and gingival condition in young adults. (4th April 2014) - Mizutani, S.; Ekuni, D.; Tomofuji, T.; Azuma, T.; Kataoka, K.; Yamane, M.; Iwasaki, Y.; Morita, M.
<x xml:space="preserve">Abstract</x> Background and Objective Xerostomia is a subjective symptom of dryness in the mouth. Although a correlation between xerostomia and oral conditions in the elderly has been reported, there are few such studies in the young adults. The aim of this study was to examine the relationship of xerostomia with the gingival condition in university students. Material and Methods A total of 2077 students (1202 male subjects and 875 female subjects), 18–24 years of age, were examined. The disease activity and severity of the gingival condition were assessed as the percentage of teeth with bleeding on probing (%BOP) and the presence of teeth with probing pocket depth of ≥ 4 mm, respectively. Additional information on xerostomia, oral health behaviors, coffee/tea intake and nasal congestion was collected via a questionnaire. Path analysis was used to test pathways from xerostomia to the gingival condition. Results One‐hundred and eighty‐three (8.8%) students responded that their mouths frequently or always felt dry. Xerostomia was related to %BOP and dental plaque formation, but was not related to the presence of probing pocket depth ≥ 4 mm. In the structural model, xerostomia was related to dental plaque formation (p < 0.01), and a lower level of dental plaque formation was associated with a lower %BOP. Xerostomia was associated with coffee/tea intake (p < 0.01) and nasal congestion (p < 0.001). Conclusion Xerostomia was indirectly related to gingival disease activity through the accumulation of dental plaque. Nasal congestion and coffee/tea intake also affected xerostomia. These findings suggest that xerostomia should be considered in screening for gingivitis risk in young adults.